2008
DOI: 10.1185/03007990802297495
|View full text |Cite
|
Sign up to set email alerts
|

Cryopyrin-associated periodic syndromes: development of a patient-reported outcomes instrument to assess the pattern and severity of clinical disease activity

Abstract: C o p y r i g h t I n f o r m a U K L i m i t e d 2 0 0 8 N o t f o r S a l e o r C o m e r c i a l D i s t r i b u t i o n U n a u t h o r i z e d u s e p r o h i b i t e d . A u t h o r i s e d u s e r s c a n d o w n l o a d , A B S T R A C TObjective: Development of an instrument for characterization of symptom patterns and severity in patients with cryopyrin-associated periodic syndromes (CAPS). Methods: Two generations of daily health assessment forms (DHAFs) were evaluated in this study. The first-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Based on the collected evidence for excessive contact system activation in FACAS, we initiated a short treatment course over 4 consecutive days with the bradykinin B2 receptor antagonist icatibant in the index patient (patient #1). Individual symptoms were assessed by a patient-reported standardized daily health assessment form that was adapted from a validated tool for CAPS 23 . Within 30 min after the first administration of 30 mg icatibant, the generalized urticarial rash and systemic symptoms improved.…”
Section: Characteristicmentioning
confidence: 99%
“…Based on the collected evidence for excessive contact system activation in FACAS, we initiated a short treatment course over 4 consecutive days with the bradykinin B2 receptor antagonist icatibant in the index patient (patient #1). Individual symptoms were assessed by a patient-reported standardized daily health assessment form that was adapted from a validated tool for CAPS 23 . Within 30 min after the first administration of 30 mg icatibant, the generalized urticarial rash and systemic symptoms improved.…”
Section: Characteristicmentioning
confidence: 99%
“…Because of the variable nature of symptoms and severity in CAPS, it is often difficult to accurately assess the quality of life of CAPS patients. Daily health assessment forms have been developed that reliably capture disease severity or symptoms and can be used to measure treatment efficacy [77]. …”
Section: Treatmentmentioning
confidence: 99%
“…This study demonstrated clear clinical and laboratory responses similar to those observed with daily anakinra 105 and was the foundation for the first randomized, placebo-controlled trial in 44 patients with FCAS and MWS 18 using a novel, validated, self-reporting daily diary to derive a key symptom score that was the primary clinical end point of the study. 106 Significant differences were observed between active drug and placebo in key symptom scores, number of flares, and CRP and SAA concentrations in both the treatment and withdrawal phase of this 2-part multicenter study in the United States. The primary side effect noted was injection-site reactions in the treatment group that never resulted in drug discontinuation.…”
Section: Newer Il-1-targeted Therapies In Patients With Capsmentioning
confidence: 79%